Gambaran Rasisme dan Perbudakan Dalam Novel the Adventure of Huckleberry Finn Karya Mark Twain - Leonarqi, Biaggie Caesar (Calakan : Jurnal Sastra, Bahasa, dan Budaya, 2024)
This research aims to provide an overview of 19th century life in Mark Twain's The Adventure of Huckleberry Finn from the conflict experienced by the main character. The method used in this research is descriptive qualitative and objective approach, with the data collection method of reading and note taking. The results of this study found that life in the 19th century described in the novel The Adventure Of Huckleberry Finn shows the life of American society which is very full of racism and slavery of white people against black people.